FOOD AND FEEDING OF CHOCOLATE MAHSEER (NEOLISSOCHEILUS HEXAGONOLEPIS) FROM FRY TO JUVENILE STAGES IN CAPTIVITY - DEBAJIT SARMA, DEBAJIT; SANWAL, SUMAN; DAS, PARTHA (Journal of the Inland Fisheries Society of India, 2021)
Chocolate mahseer, Neolissochilus hexagonolepis was reared from the juvenile stages in captivity to establish it as a new candidate species in hill aquaculture. Gut content analysis of fry showed that the food consisted of 50.48 % zooplankton, 29.72 % phytoplankton, unidentified matter 14.09 % and 5.71 % sand and mud. In fingerling stage, 56.33 % phytoplankton and 24.07 % zooplankton was recorded from the gut. Maximum phytoplankton percentage (60.65) was recorded during juvenile stage. The RLG (1.048 to 2.72) and GSI (3.92 to 9.65) accessed from fry till juvenile stage indicated the changing feeding habits from carni-omnivorous to herbi-omnivorous. Key words: Chocolate mahseer, food and feeding, captive rearing, Himalaya